COMPARISON OF PAIN CONTROL EFFECT OF TAPENTADOL AND NAPROXENSODIUM AFTER THIRD MOLAR EXTRACTIONS – A RANDOMIZED DOUBLE-BLIND SPLIT-MOUTH STUDY (Journal of Medical & Health Sciences Review, 2025)
Introduction: The surgical removal of impacted mandibular third molars is a common procedure in oral and maxillofacial surgery and is associated with varying degrees of postoperative discomfort. Pain, trismus, and swelling are frequent complaints, that significantly impact a patient’s quality of life post-surgery. To address this issue, effective pain management is essential. This study compares the effectiveness of  an opioid(tapentadol) and non-steroidal anti-inflammatory drug (Naproxen Sodium) in managing pain after impacted third molar extractionsMaterials and Methods: A randomized, double-blind, split-mouth study was conducted on 186 patients. Patients were divided into two groups of 93, with one group receiving Tapentadol and the other Naproxen Sodium. Pain levels were assessed on postoperative days one and three using a Visual Analog Scale (VAS).Results: The findings indicate no statistically significant difference in pain control between the two drugs on postoperative day one. However, Tapentadol demonstrated slightly greater efficacy on postoperative day three, with more patients reporting no pain compared to Naproxin Sodium.Conclusion: While both drugs provided effective pain relief, Tapentadol showed marginal superiority on day three. Future studies with larger sample sizes are recommended to explore this finding further.